Distribution of Bisphenol a Diglycidyl Ether (BADGE) and Its Derivatives in Indoor Dust from Various Micro-environments in Hanoi, Vietnam - Nguyen, Ta Thuy; Vu, Le; Chau, Chu Ngoc; Thanh Huyen, Nguyen Thi; Long, Dang Van; Hoa, Phung Duc; Minh, Tu Binh; Yen, Dao Thi Hai; Tri, Tran Manh (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 4, 2024)
In this report, the method for the determination of BADGE and its derivatives in dust samples has been optimized. The recoveries of the surrogate standard ( d6 -BADGE) and target compounds (in matrix spiked) were in the ranges of 78.5–99.0% and 75.4–116% (SD < 10.0), respectively. Total concentrations of BADGEs in indoor dust ranged from no detection (ND) to 6640 ng/g (mean: 950 ng/g and median: 434 ng/g). The mean (median) concentrations of four BADGEs in indoor dust samples collected from public places, homes, laboratories, and offices were 1630 (830), 957 (434), 707 (375), and 344 (170) ng/g, respectively. Among BADGEs, BADGE.2H 2 O was found at the highest levels with the ranges of ND–4880 ng/g (mean: 634, and median: 247) in indoor dust from all micro-environments. A significant correlation existed between the sum concentrations of two pairs: BADGE + BADGE.H 2 O and BADGE.2H 2 O + BADGE.HCl.H 2 O. Based on the measured concentration of BADGEs in indoor dust, the estimated exposure doses to BADGEs through dust ingestion were respectively in ranges of 0.406-1.92 and 0.351–1.66 ng/kg-bw/d for women and men.